Poincaré Map and Periodic Solutions of First-Order Impulsive Differential Equations on Moebius Stripe - Yefeng He; Yepeng Xing (Abstract and Applied Analysis)
This paper is mainly concerned with the existence, stability, and bifurcations of periodic solutions of a certain scalar impulsive differential equations on Moebius stripe. Some sufficient conditions are obtained to ensure the existence and stability of one-side periodic orbit and two-side periodic orbit of impulsive differential equations on Moebius stripe by employing displacement functions. Furthermore, double-periodic bifurcation is also studied by using Poincaré map.